2018
DOI: 10.7717/peerj.5157
|View full text |Cite
|
Sign up to set email alerts
|

Reference norms for evaluating maximum expiratory flow of children and adolescents of the Maule Region in Chile

Abstract: BackgroundThe norms for evaluating the maximum expiratory flow (MEF) usually are developed according to chronological age and height. However, to date, little research has been conducted using reference values that take into account the temporal changes of biological maturation. The objectives of this study were to (a) compare the MEF with those of other international studies, (b) align the MEF values with chronological and biological age, and (c) propose reference standards for children and adolescents.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…The results of this study are corroborated with research carried out with African American [ 19 ], Japanese [ 20 ], East Indian, Chinese [ 21 ], and Chilean [ 8 ] children. In these studies, the variability of the MEF was clearly visible between these pediatric populations from different parts of the world.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The results of this study are corroborated with research carried out with African American [ 19 ], Japanese [ 20 ], East Indian, Chinese [ 21 ], and Chilean [ 8 ] children. In these studies, the variability of the MEF was clearly visible between these pediatric populations from different parts of the world.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, altitude played a key role in the mechanical properties of the respiratory muscles, as the students in this research presented lower body size than their low altitude counterparts in Spain, Italy, and Chile [ 6 , 7 , 8 ]. Furthermore, other studies focusing on moderate altitudes have shown that these populations tend to present a slight delay in growth and somatic maturation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations